Back Cover: DNP‐Supported Solid‐State NMR Spectroscopy of Proteins Inside Mammalian Cells (Angew. Chem. Int. Ed. 37/2019). Issue 37 (25th July 2019) - Narasimhan, Siddarth; Scherpe, Stephan; Lucini Paioni, Alessandra; van der Zwan, Johan; Folkers, Gert E.; Ovaa, Huib; Baldus, Marc
Abstract : Dynamic nuclear polarization (DNP) enhanced solid‐state NMR (ssNMR) spectroscopy enables atomic‐level structural studies of isotope labeled proteins at physiologically relevant concentrations in mammalian cells, irrespective of the tumbling rate of the protein of interest, as reported by H. Ovaa, M. Baldus, and co‐workers in their Communication on page 12969 ff. In the absence of DNP, NMR sensitivity levels are insufficient to conduct such studies.